Exploiting the lubricating and anti-corrosive functionalities of graphite particles to improve the wear and corrosion resistance of the cobalt matrix - Mahshid Tafreshi; Soheil Mahdavi; Mir Saman Safavi (Journal of Materials Research and Technology)
The improved surface functions, in particular resistance of the surface to both wear and corrosion, are sought in harsh environment applications. In this study, the surface of the carbon steel was finished by Co-Graphite (Gr) composite coatings galvanostatically electrodeposited from a sulfate bath containing 0–10 g/L of Gr particles at a constant current density of 80 mA/cm2. The results of the microstructural analysis using field-emission scanning electron microscopy (FESEM) and X-ray diffraction (XRD) illustrated that the embedded Gr particles changed the morphology of the grains, and made surface denser without an obvious variation in the phase structure of the coatings. Electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization (PDP) assays were utilized to determine the corrosion behavior of the coatings. Results demonstrated a 160 % increase in charge-transfer resistance of the Co layer is obtained with the addition of 5 g/L Gr particles to the electrolyte. The tribological features of the layers were measured by the pin-on-disk method, and outcomes revealed a tremendous reduction in the coefficient of friction (COF) of the Co deposit, up to 80 %, upon the inclusion of the Gr particles in the coatings. The Co-Gr composite electrodeposits indicated superior tribo-corrosion performance than that of pure Co, which make them potential candidates to be used as a durable protective coating in different industries.